2016
DOI: 10.1212/wnl.0000000000003353
|View full text |Cite
|
Sign up to set email alerts
|

Stable incidence but declining case-fatality rates of subarachnoid hemorrhage in a population

Abstract: Objective: To characterize temporal trends in subarachnoid hemorrhage (SAH) incidence and outcomes over 5 time periods in a large population-based stroke study in the United States.Methods: All SAHs among residents of the Greater Cincinnati/Northern Kentucky region at least 20 years of age were identified and verified via study physician review in 5 distinct year-long study periods between 1988 and 2010. We abstracted demographics, care patterns, and outcomes, and we compared incidence and case-fatality rates … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
65
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(69 citation statements)
references
References 26 publications
1
65
3
Order By: Relevance
“…Our finding of unchanged risk of subarachnoid haemorrhage and declining mortality corroborates other findings. 36 This analysis updates our earlier data linkage study reporting decreasing mortality for intracerebral 12 and subarachnoid haemorrhage in NSW from 2001 to 2009, 13 demonstrating sustained mortality reductions for these sub-types with more recent data.…”
Section: Comparison With Other Studiessupporting
confidence: 79%
See 1 more Smart Citation
“…Our finding of unchanged risk of subarachnoid haemorrhage and declining mortality corroborates other findings. 36 This analysis updates our earlier data linkage study reporting decreasing mortality for intracerebral 12 and subarachnoid haemorrhage in NSW from 2001 to 2009, 13 demonstrating sustained mortality reductions for these sub-types with more recent data.…”
Section: Comparison With Other Studiessupporting
confidence: 79%
“…Several studies have demonstrated recent declines in stroke rates and mortality, although this experience is not universal. [30][31][32][33][34][35][36][37][38][39] Two studies utilising administrative data from England 30 and Sweden 31 While neither study included subarachnoid haemorrhage nor reported statistics separately for intracerebral and ischaemic stroke, both reported reductions in stroke incidence and mortality. Our finding of unchanged risk of subarachnoid haemorrhage and declining mortality corroborates other findings.…”
Section: Comparison With Other Studiesmentioning
confidence: 99%
“…In contrast, recent evidence for declining mortality is sparse. Two recent publications demonstrate declines in the USA ( 24 ) and England ( 25 ) for periods to 2010 and another two publications one each from the USA and UK for periods to 2008 ( 22 , 26 ), while in-hospital mortality significantly declined from 2000 to 2015 in those select SAH patients requiring intensive care in Australia and New Zealand ( 27 ). Declines in fatal SAH rates were not apparent in those aged over 70 years, suggesting that their exposure to risk factors has not altered over time.…”
Section: Discussionmentioning
confidence: 99%
“…Cigarette smoking and hypertension are notable risk factors . Mortality is higher with older age and appears to be decreasing …”
Section: Introductionmentioning
confidence: 99%
“…[8][9][10][11] Mortality is higher with older age and appears to be decreasing. 12,13 The crude incidence of SAH in Australia is estimated to be 10.3 (95% CI 10.1-10.4) per 100 000 person-years. 14 In that study, patients admitted to hospitals between 1998 and 2008 were identified in the National Hospital Morbidity Database.…”
Section: Introductionmentioning
confidence: 99%